Effect Of Product Reviews And Trust On Purchasing Decisions On The Shopee Marketplace - Mutmainah; Sri Ernawati (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Marketplace is one form of E-Commerce that is progressing rapidly in Indonesia. This research is to find out the effect of product reviews and trust on purchasing decisions in the Shoppe marketplace either partially or simultaneously. This study uses the type of Associative research. To measure the relationship between two independent and dependent variables, questionnaires are used, in which respondents are given alternative answer options for each statement. Questionnaires were distributed to the number of respondents, and all variables were measured using a Likert scale. Data analysis using validity test, reliability test, t test and f test with the help of SPSS 23.00. The result is product reviews and trust simultaneously have a significant effect partially or simultaneously on purchasing decisions on the Shopee marketplace